Linking Peregrine Falcons' (Falco peregrinus) Wintering Areas in Peru with Their North American Natal and Breeding Grounds - Beingolea, Oscar; Arcilla, Nico (The Journal of raptor research, 2020)
Identifying migratory raptors' wintering areas and migration routes is an essential part of predicting their responses to habitat and climate change throughout their annual cycles, and therefore important for their conservation. Among the world's most widespread migratory species, the Peregrine Falcon (Falco peregrinus) has been the subject of intensive study on its breeding grounds and at some migratory stopover sites, but the links between its breeding, stopover, and wintering areas remain poorly known. In particular, few empirical data are available on migratory F. p. tundrius and F. p. anatum (hereafter, Nearctic peregrines) wintering in South America during the austral spring and summer. Here, we present evidence connecting Nearctic peregrines wintering in Peru with their natal and breeding territories in North America using mark-recapture data collected between 1963 and 2019. We documented eight encounters of banded wintering Nearctic peregrines, whose natal origins or breeding regions included the Northwest Territories, Nunavut, and Yukon Territory in Canada, and Alaska, Minnesota, and Nebraska in the USA. Our findings indicate that both tundrius and anatum peregrines winter in Peru and originate from a widespread geographic breeding range, corroborating other research suggesting that Nearctic peregrine migration is highly dispersive. Peregrines exhibit sex-related differential migration patterns in which males tend to migrate farther than females, and our data from the capture of 208 Nearctic peregrines suggest that the majority of wintering birds in Peru are males (n =150; 72%). We also report new records of Nearctic peregrine arrivals in Peru that represent advances of approximately 2–3 wk compared to the earliest previously published reports. The variability of peregrines' migratory movements may be related to the behavioral plasticity that facilitated their successful recovery following their catastrophic declines in much of North America. As peregrines remain vulnerable to human impacts including habitat and climate change, continuing to fill gaps in our knowledge of Nearctic peregrines' migratory connectivity will enable continuing conservation measures for these spectacular birds.